Islamic Education Educator at As-Sunnah Islamic College Deli Serdang 2012-2024 AD (Analysis of the Historical Study of Islamic Education) - Harahap, Muhammad Sapii (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This research aims to find out the names and identities of educators at the As-Sunnah Islamic College. The historical method consists of data collection, source criticism, interpretation and finally historiography. The research approaches used in this research are the geographical approach, sociological approach, educational approach and historical education. The results of this research are that the educators presented by the researcher are in accordance with the order in the SINTA STAI As-Sunnah Account, namely: 1) Dr. Muhammad Sapii Harahap, M.Pd., Hafidzhullah, 2) Muhammad Iqbal, M.Pd.I., Hafidzhullah, 3) Suhendri, M.Sos., Hafidzhullah, 4) Slamet Riyadi, S.Pd.I., MA. , Hafidzhullah, 5) Rozaanah, MA., Hafidzhullah, 6) Dr. Daryanto Setiawan, M.Kom.I., Hafidzhullah, 7) Dr. Wagiman Manik, M.Pd.I., Hafidzhullah, 8) Dr. Sopian Sinaga, M.Pd.I., Hafidzhullah, 9) Ahmad Zaky, S.Pd.I., MA., Hafidzhullah, 10) Ade Muhammad Ritonga, M.Pd., Hafidzhullah, 11) Ilham Tumanggor, M.Si ., Hafidzhullah, 12) Dr. Bahrul Ulum, M.Pd., Hafidzhullah, 13) Arbonas Lubis, M.Pd., Hafidzhullah, 14) Tiy Kusmarrabbi Karo, MA., Hafidzhullah, 15) Dasa Syawal Syahputra, M.Sos., Hafidzhullah, 16) Hasan Hamzah Lubis, M.Sos., Hafidzhullah, 17) Ahmad Afandi, M.Pd., Hafidzhullah, 18) Irham Dongoran, Lc., M.Ag., Hafidzhullah, 19) Syahri Ramadona, M.Is., Hafidzhullah, 20) Muhammad Syarif Muda Hasibuan, Lc., M.Si., Hafidzhullah, 21) Dr. Benny Munardi, M.Kom.I., Hafidzhullah, 22) Abdul Aziz Shidiq, M.Pd., Hafidzhullah, 23) Taufik Hidayat, M.Sos., Hafidzhullah, 24) Candra Gunawan, M.Si., Hafidzhullah, 25 ) Zulham Effendi, M.Pd.I., Hafidzhullah, 26) Khairul Anhar, Lc., M.Sc., Hafidzhullah, 27) Albahroyni, M.Sos., Hafidzhullah, 28) Fakhrurrozi, S.Pd.I., M.TH., Hafidzhullah, 29) Jihan Afri Batubara, M.Sos., Hafidzhullah, 30) Ade Chairil Anwar., Hafidzhullah, 31) Indra, M.Ag., Hafidzhullah, 32) Dori Chandra, M.Sos., Hafidzhullah, 33) Arifdo Putra., Hafidzhullah, 34) Muslim, MA., Hafidzhullah, 35) Fian Triadi, M.Pd., Hafidzhullah, 36) Fachri Rinaldy, S.Pd., M.H., Hafidzhullah, 37) Dirja Hasugian, Lc., M.Ag., Hafidzhullah, 38) Ahmad Nizar, M.A., Hafidzhullah, 39) Dr. Hasanuddin Dollah Hasibuan Hafidzhullah, 40) Maulana Limbong, M.Psi., Hafidzhullah, 41) Muhajirah Binti Jamaluddin, M.TH., Hafidzhallah, and 42) Hendriansyah Hafidzahallah